Improving Junior High School Students Critical Thinking Skills in Social Studies through Contextual Teaching and Learning (CTL) Assisted by Video Media: A Classroom Action Research - Nur Sari Hidayati; Ahmad Imam Khairi (SOCIALE: International Journal of Social Studies, 2026)
The low critical thinking ability of grade VIII-A SMPN 2 Pamekasan students in social studies subjects is characterized by difficulties in solving high-level cognitive problems, low activeness in learning, and inability to relate material to real-life contexts. This study aims to determine the improvement of students' critical thinking skills through the application of the Contextual Teaching and Learning (CTL) learning model with video media. The research uses the Classroom Action Research (PTK) method with a mixed method approach which is carried out in two cycles, each including the stages of planning, action, observation, and reflection. The subject of the study is 33 students of class VIII-A SMPN 2 Pamekasan for the 2024/2025 school year. Data collection techniques include observation of teacher and student activities, critical thinking ability tests, and documentation. The research instruments are in the form of observation sheets and test questions based on Facione's critical thinking indicators, namely interpretation, analysis, evaluation, and inference. Data analysis was carried out descriptively, quantitatively, and qualitatively. The results showed that the application of the CTL model with video media was able to improve students' critical thinking skills, which was shown by an increase in classical completeness from 52% in the pre-cycle to 67% in the first cycle and 85% in the second cycle. Teacher and student activities have also increased significantly. Thus, the CTL model assisted by video media is effectively used in social studies learning.